IMPLEMENTATION OF AMONG SYSTEM A3 (ASAH, ASIH, ASUH) IN PLANTING THE VALUE OF CHARACTERS IN EARLY CHILDHOOD - Wahyuningsih, Siti; Dewi, Nurul Kusuma; Hafidah, Ruli (Universitas Sebelas Maret, 2018)
This activity was carried out in Gugus Mawar, Karanganyar Regency. The service activity aims to provide training to preschool (PAUD) and kindergarten teachers of Gugus Mawar, Karanganyar about the application of the among system (asah, asih, asuh) to instill character valuesin early childhood. The training participants consisted of 20 teachers of preschool and kindergarten in Gugus Mawar, Karangannyar. The training was carried out in three stages, namely (1) Pre-implementation, (2) Implementation, and (3) Monitoring and Evaluation. The training material were (1) material about the concept of the among system, early childhood learning, and the character valuesthat must be inculcated in early childhood; (2) learning device material that applies among systems to instill the character values of early childhood; (3) the implementation of among system in learning to instill the character values of early childhood in their respective schools. The material given during the training resulted in preschool and kindergarten teachers in Gugus Mawar, Karangannyar being able to develop learning instrument, carry out learning, and instill character valuesin early childhood by implementing the among (asah, asih, asuh) systems.